Telling My Tale: Reflections on the Process of Visual Storytelling for Children and Youth Living With Cystic Fibrosis and Muscular Dystrophy in Canada. (21st January 2020) - Moola, Fiona J.; Moothathamby, Nivatha; McAdam, Laura; Solomon, Melinda; Varadi, Robert; Tullis, Diana Elizabeth; Reisman, Joe
Storytelling is perennial to the human condition. We all tell stories and we all bear witness to the stories of others. According to narrative scholars, only certain stories are valorized in contemporary culture, while others go unrecognized. The inability to recognize ourselves and identities in contemporary cultural narratives can contribute to the silencing and muting of certain lives and voices. Young people with life-shortening conditions, such as cystic fibrosis (CF) and muscular dystrophy (MD), are rarely afforded the opportunity to have their stories heard and affirmed in contemporary cultural spaces. In this article, we reflect on the methodological process of engaging in a study known as "Telling My Tale, " that is, a storybook study featuring narratives and artwork by young people with CF and MD. Funded by the Social Sciences and Humanities Research Council of Canada, we critically reflect upon the methodological lessons, advances, and innovations we have learned, including theoretical musings, the process of exhibiting some of the artwork in a public art gallery, challenges faced along the way, analytical conundrums, and the role of technology in artistic creation for participants with limited hand function. In so doing, we hope to further methodological and theoretical development and innovation in narrative and artistic traditions to better center the voices, lives, tales, and experiences of young people with life-shortening conditions.